Metabolism of imidacloprid and DDT by P450 CYP6G1 expressed in cell cultures of Nicotiana tabacum suggests detoxification of these insecticides in Cyp6g1-overexpressing strains of Drosophila melanogaster, leading to resistance. - Joußen, N.; Heckel, D.G.; Haas, M.; Schuphan, I.; Schmidt, B. (Pest Management Science, 2008)
With the worldwide use of insecticides, an increasing number of pest insect species have evolved target-site or metabolism-based resistance towards some of these compounds. The resulting decreased efficacy of pesticides threatens human welfare by its impact on crop safety and further disease transmission. Environmental concentrations of some insecticides are so high that even natural populations of non-target, non-pest organisms such as the fruit fly Drosophila melanogaster Meig. have been selected for resistance. Cyp6g1-overexpressing strains of D. melanogaster are resistant to a wide range of chemically diverse insecticides, including DDT and imidacloprid. However, up to now there has been no evidence that the CYP6G1 enzyme metabolises any of these compounds.Here it is shown, by heterologous expression in cell suspension cultures of Nicotiana tabacum L. (tobacco), that CYP6G1 is capable of converting DDT (20 microg per cell culture assay) by dechlorination to DDD (18% of applied amount in 48 h), and imidacloprid (400 microg) mainly by hydroxylation to 4-hydroxyimidacloprid and 5-hydroxyimidacloprid (58 and 19% respectively in 48 h).Thus, the gap between the supposed resistance gene Cyp6g1 and the observed resistance phenomenon was closed by the evidence that CYP6G1 is capable of metabolising at least two insecticides.